The Determinants of Intra-Firm Trade: In Search for Export-Import Magnification Effects - Peter Egger; Michael Pfaffermayr (Kiel Institute for World Economics (IfW), 2005)
This paper studies the determinants of Austrian bilateral intra-firm trade in a panel of industry-level intra-firm goods trade flows. Economic size, unit labor costs and the magnification effects originating from multiple border crossing of sequentially finished products are found to be the most important determinants of trade within multinational firms. Especially, our evidence lends support to multiple border crossing of sequentially finished products, an argument that recently has been put forward in the outsourcing literature.
Keywords: 330; Firmeninterner Handel; Multinationales Unternehmen; Globalisierung; Schätzung; Österreich